The United States requires effective federal policy to reduce marine plastic pollution. Issue 6 (23rd April 2019) - Iverson, Autumn R.
Abstract: The amount of plastic entering the ocean is expected to increase by an order of magnitude by 2025. Marine plastic pollution threatens biodiversity through entanglement, ingestion, and chemical exposure. The United States is in the top 20 of 192 coastal countries with mismanaged waste entering the ocean. This paper addresses U.S. policies regarding single‐use plastics and fishing nets, two major sources of plastic pollution. Currently, the United States does not have a federal ban on most single‐use plastics or on synthetic gillnets. This paper recommends a federal ban on single‐use plastics, alternative material for fishing nets and/or increased regulations, more research into the ecological and policy considerations of plastic pollution, continuing cleanup efforts and learning from policy challenges faced by other countries. The United States can look to the recent European Plastics Strategy as a leading example of large‐scale policy initiatives to reduce marine plastic pollution.